LITERATURE REVIEW: PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN - Agatania Rilly Gwyneth; Amalia Natalia Watulangkow; Marselina Laenus; Marssel Michael Sengkey (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
In carrying out their duties, employees often face various problems, causing their performance to decline. With the decline in employee performance, the company's income will gradually decrease. One factor that can affect employee performance is leadership. The purpose of this study is to investigate the effect of transformational leadership style on employee performance. The technique used was to review written works and conduct research based on various previous journals, with a particular focus on transformational leadership and job satisfaction. Information was collected using search engines such as Semantic Scholar and Google Scholar. In this study, 20 scientific articles were used as sources of information. The inclusion criteria in this review were specifically defined, namely that articles must discuss transformational leadership and its direct impact on employee performance. Conversely, exclusion criteria were applied to articles that only discussed one variable, for example, only discussing leadership style without linking it to employee performance, or vice versa. This approach ensured that the selected literature truly supported the research focus so that the review results were more focused and comprehensive. The results of the study show that transformational leadership has a positive influence due to its efficient leadership style, with clear communication that can be applied in various fields.